2004
DOI: 10.2519/jospt.2004.34.11.725
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Treatment Approach Emphasizing Impairment-Based Manual Physical Therapy for Plantar Heel Pain: A Case Series

Abstract: Study Design: Case series. Objective: To describe an impairment-based physical therapy treatment approach for 4 patients with plantar heel pain. Background: There is limited evidence from clinical trials on which to base treatment decision making for plantar heel pain. Methods and Measures: Four patients completed a course of physical therapy based on an impairment-based model. All patients received manual physical therapy and stretching. Two patients were also treated with custom orthoses, and 1 patient recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
3
30
0
1
Order By: Relevance
“…[9][10][11]15 Only weak evidence exists to support the use of manual therapy interventions and therapeutic exercise in the patient population with plantar heel pain. 27,41 No randomized trials of manual therapy interventions have been reported. Young et al 41 reported the outcomes of a series of 4 patients with heel pain who were managed with manual physical therapy, which was augmented by therapeutic exercise.…”
Section: Examination Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…[9][10][11]15 Only weak evidence exists to support the use of manual therapy interventions and therapeutic exercise in the patient population with plantar heel pain. 27,41 No randomized trials of manual therapy interventions have been reported. Young et al 41 reported the outcomes of a series of 4 patients with heel pain who were managed with manual physical therapy, which was augmented by therapeutic exercise.…”
Section: Examination Proceduresmentioning
confidence: 99%
“…27,41 No randomized trials of manual therapy interventions have been reported. Young et al 41 reported the outcomes of a series of 4 patients with heel pain who were managed with manual physical therapy, which was augmented by therapeutic exercise. Although all patients received 7 or fewer treatments in physical therapy, they all reported a clinically meaningful reduction in pain and improvement in function.…”
Section: Examination Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Young et al 61 reported on 4 patients referred to physical therapy for plantar fasciitis or unilateral -rating scale and a self-reported function scale to assess out--scribed foot orthoses and another patient received additional --a rapid improvement in pain and function as a result of the 38 reported on 1 patient referred to physical therapy for plantar fasciitis with an 8-month history of subcalcaneal heel pain that limited standing the straight-leg raising (SLR) test in combination with ankle dorsiflexion and eversion to sensitize the tibial nerve, suggesting that there was a neurogenic component to this paappear consistent with the findings of Coppieters and associates 11 who reported significant strain and excursion of the tibial nerve in 8 embalmed cadavers when ankle dorsiflexion 38 received passive and active mobilization aimed at restoring pain-free soft tissue mobility along -tion procedures were performed with the patient in the slump sitting position. Because restricted ankle dorsiflexion, excessive pronation, and posterior tibialis weakness were also found, low-Dye taping and therapeutic exercises were utilized to control excessive pronation and reduce stress on the plantar fascia.…”
Section: IVmentioning
confidence: 99%